ΕΔΑΦΙΚΕΣ ΔΙΕΚΔΙΚΗΣΕΙΣ ΤΗΣ ΒΕΝΕΤΙΑΣ ΣΤΗ Ν. ΜΕΣΣΗΝΙΑ (Α’ ΜΙΣΟ ΤΟΥ 15ΟΥ ΑΙΩΝΑ). ΜΕ ΑΦΟΡΜΗ ΑΝΕΚΔΟΤΟ ΑΡΓΥΡΟΒΟΥΛΛΟ ΤΟΥ ΘΩΜΑ ΠΑΛΑΙΟΛΟΓΟΥ - ΠΑΠΑΚΟΣΜΑ ΚΩΝΣΤΑΝΤΙΝΑ Δ. (Eoa kai Esperia, 2007)
The present paper deals with Venice’s long and strenuous diplomaticefforts during the first half of the 15th century to extend its rule over theMessenian hinterland, by acquiring certain strongholds subject to theprincipality of Achaea, such as Navarino, Grisi, Maniatochori (Manticuor),Cosmina and Lachanada (Canada/La Cannata). Special emphasis is put on the Venetian claim for two of them, Grisi andManiatochori, in southern Messenia. Two, unpublished so far, documents,conserved in Venice’s State Archives, namely a) a copy of an argyrovullon ofthe Greek despot of Morea Thomas Palaeologos, issued in July 1454 and b)another one of a public proclamation made by the Venetian castellan ofModon, Alexandra Marcello, later in the same year, cast new light on theexact time and the conditions, under which Venice succeeded in takingpossession of the two above-mentioned Messenian places. According to thetwo documents, the Venetian occupation of Grisi and Maniatochori wasofficially established in 1426 by a privilegio of Centurione II Zaccaria andlasted until 1450, when the two villages were captured by ThomasPalaeologos. Eventually, in 1454 they were restored to Venice by theargyrovullon of the Greek despot.